The Charlson Comorbidity Index and depression are associated with satisfaction after short-segment lumbar fusion in patients 75 years and older - Wang, Shuai-Kang; Mu, Hong; Wang, Peng; Li, Xiang-Yu; Kong, Chao; Cheng, Jing-bo; Lu, Shi-Bao; Zhao, Guo-Guang (Frontiers in Surgery, 2022)
Background. The rate and volume of lumbar spinal fusion(LSF) surgery performed for patients aged 75 years and older increased in recent years. The purposes of our study were to identify factors associated with postoperative dissatisfaction and evaluate the predictive value of comprehensive geriatric assessment(CGA) for dissatisfaction at 2 years after elective short-segment LSF in patients aged 75 and older. Methods. This was a retrospective study using a prospectively collected database of consecutive patients(aged 75 and older) who underwent elective LSF for degenerative diseases from June 2018 to May 2020. Preoperative CGA consisting six domains was performed for each patient 1 day before the operative day. Univariate and multivariate analyses were performed to identify factors that predict for dissatisfaction with surgical treatment. The primary outcome was patient satisfaction with LSF, as measured by the North American Spine Society(NASS) satisfaction scale. Secondary outcomes included postoperative complications, the length of stay, visual analog scale(VAS), and Oswestry Disability Index. Results. A total of 211 patients were available for a follow-up at 2 years and included in our final study cohort with a mean age of 80.0 years. A total of 175 patients(82.9%) were included in the satisfied group, and 36 patients (17.1%) were included in the not dissatisfied group. In the dissatisfied group, there was a higher incidence of postoperative complications(30.6% vs 14.3%, p = 0.024) and greater VAS scores for lower back (4.3  1.9 vs 1.3  1.4, p = 0.001) and leg(3.9  2.1 vs 0.9  1.3, p = 0.001). Multivariate regression analysis revealed that patients with greater CCI score(odd ratio [OR] 2.56, 95%CI 1.12-5.76; p=0.030 for CCI 1 or 2 and OR 6.20, 95%CI 1.20-28.69; p = 0.024), and depression(OR 3.34, 95%CI 1.26-9.20; p = 0.016) were more likely to be dissatisfied compared with patients with the CCI score of 0 and without depression. Conclusions: Satisfaction after LSF in older patients was similar to that of previously reported younger patients. Preoperative depression and higher CCI scores were independent risk factors for postoperative dissatisfaction two years after LSF. These results help inform decision-making when considering LSF surgery for older patients.